Gift and Exchange between Disciplines (KULT_online, 2020)
This review concerns the volume Gabe und Tausch: Zeitlichkeit, Aisthetik, Ästhetik, a book worth reading. The volume maps the interdisciplinary field of research into the relationship between gift and exchange. The focus lies on the differentiation and interrelation of those concepts with special regard to their temporality and aesthetics.